Managing technological innovation : competitive advantage from change - Betz, Frederick (Wiley, 2011)
"Frederick Betz is one of the original creators of "technology management" and was Director of the TM program at the NSF. His first book on Management of Technology published by Prentice Hall 16 years ago has been acknowledged as setting the foundation for the subject. Betz further helped crystalize the field of technology management and the management of innovation with the first two editions of Managing Technological Innovation. With this third edition he will bring the subject inline with current business strategy. This edition will present information in a newer organized format that aligns more closely with how the topics are presented and discussed in the classroom. Planned for inclusion will be a greater discussion of how science and technology interact with the global economy"--